Homeostasis An Integrated Vision - Lasakosvitsch, Fernanda; Dos Anjos Garnes, Sergio (IntechOpen, 2019)
The human body is composed of several systems and organs, consisting of millions of cells that need relatively stable conditions to function and contribute to the survival of the body as a whole. The maintenance of stable conditions for the cells against the variations of the external environment is an essential function of the body and is called homeostasis. As a consequence of the loss of homeostasis, a disease is manifested. This book aims to provide the reader with an up-to-date view of the self-regulatory mechanisms that are activated to achieve homeostasis, the pathways that are altered during the disease process, and how medicine can intervene to restore balance in critical patients.